Improved Patient Outcomes with Electrocauterization Following Wedge Resection and Curettage for Ingrown Toenails: A Prospective Comparative Study - Amarin, Marzouq; Al-Taher, Raed; Daradka, Khaled; Abu Harb, Amal Ibraheem Abd al Qader; Habashneh, Rawan Abd AlMohsen Mohammad; Bustami, Nadwa Basem; Hijazein, Yazan; Hadadin, Hiba; Al-Najjar, Sondos Wa'el Sa'dat (Archives of Plastic Surgery, 2024)
Background Ingrown toenail is a common condition that results in chronic pain, recurrent infections, and difficulty in performing daily activities. Our aim is to compare two surgical methods for the treatment of ingrown toenails: wedge resection with curetting versus wedge resection curetting followed by electrocauterization of the nail bed.Methods A prospective, comparative study that included 130 patients with ingrown toenails. All patients had stage II or III disease. We divided the participants into two groups according to the type of surgery and all patients were followed up for 6 months. The outcomes measured were the incidence of postoperative bleeding and infection, recovery time, patient satisfaction, and recurrence rate 6 months after surgery.Results Of the 130 patients included, 59 (45.4%) underwent excision and curetting of the nail matrix (group 1) and 71 (54.6%) underwent excision, curetting, and electrocauterization of the nail matrix (group 2). The postoperative infection rates were 20.3 and 4.2% in the first and second groups, respectively (p = 0.004). Patient satisfaction was 76.3% among the first group, while 91.5% of patients in the second group were satisfied with the results of surgery. Six months postoperatively, recurrence rates were 25.4 and 4.2% in the first and second groups, respectively (p = 0.001).Conclusion Wedge excision and curettage, followed by electrocauterization of the ingrown toenail is a safe treatment modality with a high success rate, that is evident by a lower recurrence rate, and greater patient satisfaction, with no effect on postoperative pain score or recovery time.
Keywords: ingrown nails; electrocautery; curettage; excision; onychocryptosis